1981
DOI: 10.1016/s0006-291x(81)80107-6
|View full text |Cite
|
Sign up to set email alerts
|

Saturation behavior of superoxide dismutation catalyzed by the iron containing superoxide dismutase of E. coli B

Abstract: The iron containing superoxide dismutase from E. coli B is shown to catalyze superoxide dismutation by a mechanism which exhibits saturation kinetics. This behavior is quite different from that observed previously with bovine Zn/Cu-and iron-containing superoxide dismutase from P. leiosnathi. Two parameters of catalysis were measured in the pH range 7.2 to 10.4: k was found to be independent of pH and Km varied with the function Km = K~ow pH) [i + exp(pH-8.8)]. These results implicate a group in the catalytic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…Thus where k 4 and k -4 are the rate constants describing the forward and backward rates of the Fe 2+ (H 2 O)‚O 2 •-+ H + S Fe 3+ (OH -) + H 2 O 2 reaction (15,21), with the subscripts mut and opt indicating whether the rate constant in question pertains to a mutant or WT-FeSOD. Assuming that the backward reaction accelerates by a factor similar to that by which the forward reaction decelerates (54) in the case of a low reorganization energy as supported by SOD's rapid turnover and very similar oxidized and reduced state crystal structures (13,55,56), we obtain Thus, a plot of the predicted percent activity retained, as a function of the shift in E m , is provided in Figure 6. On the basis of this highly simplified model, our measured shifts in E m should produce catalytic activities 33% and <5% of that of WT-FeSOD, for Q69H-and Q69E-FeSOD, respectively.…”
Section: Q69h-fesodmentioning
confidence: 98%
“…Thus where k 4 and k -4 are the rate constants describing the forward and backward rates of the Fe 2+ (H 2 O)‚O 2 •-+ H + S Fe 3+ (OH -) + H 2 O 2 reaction (15,21), with the subscripts mut and opt indicating whether the rate constant in question pertains to a mutant or WT-FeSOD. Assuming that the backward reaction accelerates by a factor similar to that by which the forward reaction decelerates (54) in the case of a low reorganization energy as supported by SOD's rapid turnover and very similar oxidized and reduced state crystal structures (13,55,56), we obtain Thus, a plot of the predicted percent activity retained, as a function of the shift in E m , is provided in Figure 6. On the basis of this highly simplified model, our measured shifts in E m should produce catalytic activities 33% and <5% of that of WT-FeSOD, for Q69H-and Q69E-FeSOD, respectively.…”
Section: Q69h-fesodmentioning
confidence: 98%
“…In this mechanism the inactive inhibitor-bound enzyme is six-coordinated, while the active form remains five-coordinated, with substrate binding causing the displacement of one of the manganese ligands. A third proposed mechanism suggested that the catalytic reaction occurs through an outer sphere mechanism and instead utilizes an alternate anion-binding site in the active site, possibly at the base of the funnel [216218]. This proposal is based upon various anions inhibiting the activity of FeSOD, but without directly coordinating the metal center.…”
Section: Manganese and Iron Superoxide Dismutasesmentioning
confidence: 99%
“…The more extensively studied metalloenzyme, superoxide dismutase (SOD), disproportionates O 2 − to afford H 2 O 2 and O 2 . 204,216 The active site's redox potential and access to protons would be the two most important parameters governing this chemistry. The metal ion of SOR sits at the surface of the protein exposed to solvent.…”
Section: Active Site Structure and Mechanismmentioning
confidence: 99%